PENGARUH PERSEPSI KUALITAS PELAYANAN KANTOR PAJAK BAGI WAJIB PAJAK ORANG PRIBADI, TARIF PAJAK DAN ATURAN PAJAK TERHADAP TINGKAT KEPATUHAN DALAM MELAPORKAN PAJAK PENGHASILAN DI KPP MADYA TANGERANG - Rananda Septanta (Universitas Pamulang, 2017)
By using the sample of taxpayers of individuals registered in KPP Madya Tangerang. Researchers test whether there is influence from the Perceptions of Quality of Tax Office Services for Individual Taxpayer, Tax Rate and Application of e-SPT Against Compliance Rate In Reporting Income Tax In KPP Madya Tangerang. Data is analyzed by using SPSS. Based on the existing analysis, it is evident that the variable of service quality does not affect the level of compliance in reporting income tax in KPP Madya Tangerang. However, the variable tax rate and Application of e-SPT in this case have an influence on tax compliance level, especially in reporting income tax at KPP Madya Tangerang.